Hope gone awry—An odd bed fellowship of Islamic and Christian neo‐apocalypticism. Issue 1 (22nd December 2021) - Kärkkäinen, Veli‐Matti
Abstract: While the rise of neo‐apocalypticism, as it is called in Christian parlance, is a well‐known phenomenon to theologians and other scholars observing the current global religious landscape, the significance of neoapocalypticism in Islam is a less well‐known fact. Yet–and this makes the topic so significant theologically–between these two forms of intense eschatological expectations, astonishing cross‐breeding is taking place. This is counterintuitive in light of the fact that in many ways Islamic and Christian neo‐apocalyptic visions seem to be totally hostile towards each other. This article introduces both Islamic and Christian neo‐apocalypticisms and reflects on the implications of their co‐existence and mutual exchanges for the future of interfaith relations and global peace.